The effect of hydrogen on the breakdown of the protective oxide scale in solid oxide fuel cell interconnects. (February 2021) - Gunduz, Kerem O.; Chyrkin, Anton; Goebel, Claudia; Hansen, Lukas; Hjorth, Oscar; Svensson, Jan-Erik; Froitzheim, Jan
Highlights: Dual atmosphere exposures with and without pre-oxidation on AISI 441 steel. The most severe corrosion damage ocurred at 600 °C. Cr diffusion is the critical parameter affecting protectiveness. Hydrogen is believed to mitigate Cr diffusion at the grain boundaries. The discrepancies in the literature on the dual atmosphere effect are discussed. Abstract: In this study, the effect of hydrogen, on the degradation of AISI 441 interconnect, under solid oxide fuel cell operating conditions was investigated between 500−800 °C for 336 h. As a new hypothesis, it is concluded that, hydrogen impedes Cr diffusion, probably in the grain boundaries, leading to the breakdown of the protective oxide scale. This effect is most severe at 600 °C, while at lower or higher temperatures the effect is attenuated. Cr diffusion is enhanced at high temperatures, whereas protective scales can be obtained at low temperatures with a lower amount of Cr.